2018
DOI: 10.1016/j.ssmph.2018.04.004
|View full text |Cite|
|
Sign up to set email alerts
|

Women’s spousal choices and a man’s handshake: Evidence from a Norwegian study of cohort differences

Abstract: Both high grip strength and being married independently relate to better functional capacity and health at older ages, but the combined effect of marital status and strength have not been investigated. Especially at older ages, declining strength can have adverse health and social consequences, where having a spouse could potentially help with everyday support and alleviate some of the negative effects of sarcopenia. We investigate how grip strength relates to being married among two cohorts of 59–71 year olds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…It is also uncertain how ongoing changes in the prevalence of particular family constellations (e.g., increases in divorce and cohabitation along cohort lines) may change the relationship between marital status trajectories and later-life cognitive impairment. Norwegian data have suggested that the selection of people—particularly men—into marriage based on grip strength has increased for younger cohorts ( Skirbekk et al, 2018 ), suggesting that the relationship between being unmarried and health may be even stronger in younger cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…It is also uncertain how ongoing changes in the prevalence of particular family constellations (e.g., increases in divorce and cohabitation along cohort lines) may change the relationship between marital status trajectories and later-life cognitive impairment. Norwegian data have suggested that the selection of people—particularly men—into marriage based on grip strength has increased for younger cohorts ( Skirbekk et al, 2018 ), suggesting that the relationship between being unmarried and health may be even stronger in younger cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Nishitani et al found that diabetes mellitus patients had a lower muscle strength 68 . Also some studies reported effects of age, gender and marital status and socio‐economic status on physical performance 69‐72 . Therefore, since these variables could affect the results, we excluded them to assess the independent effect of HLS on CRF and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known about how major life transitions, such as bereavement, affect different measures of intrinsic capacity. In previous studies, an association between marital status and grip strength has been reported [13,14], but whether spousal bereavement is causally related to grip strength is as far as we know unknown. Moreover, the causal impact of spousal bereavement on cognition, one of the other pillars of intrinsic capacity, is inconsistent [15].…”
Section: Introductionmentioning
confidence: 92%